Data and Reporting Quality in Tympanoplasty and Ossiculoplasty Studies. (August 2017) - Lailach, Susen; Zahnert, Thomas; Neudert, Marcus
Objective: The objective of our study was to check the documentation of hearing outcome parameters and influencing factors (surgical, pathological, and methodological) in published literature evaluating hearing outcome after tympanoplasty. We aimed to assess how effectively the American Academy of Otolaryngology—Head and Neck Surgery (AAO-HNS) 1995 guidelines were applied. Study Design: Retrospective noncontrolled study. Setting: Ear research center. Subjects and Methods: This study was based on a PubMed research, including peer-reviewed English-speaking original studies published from January 2005 to December 2015. In total, 169 studies were checked for correct description of study population, surgical methodology, study design, and documentation of the hearing outcome. In addition, the correct application of AAO-HNS 1995 criteria was checked. Results: Pre- and postoperative air-bone gap were shown as mean ± standard deviation in half of all series (52% vs 56%). The recommended frequency spectrum (0.5-3 kHz) was used in 46%, while a documentation of frequency spectrum was available in 85%. Whereas a statement on presence of stapes suprastructure (81%) and initial pathology was usually available, mucosa status (17%) and aeration (8%) were only shown in few series. Revision cases, staged cases, and myringoplasty graft material were documented in 46% to 57%. Type and material of prosthesis were represented in 74% to 82%. None of the publications analyzed fulfilled all 10 AAO-HNS criteria. In 10%, 7 to 9 criteria were used correctly. Conclusion: A heterogeneous description of surgical and pathological findings and the application of minimal reporting standards are essential preconditions to enable comparisons between different studies and to generate meta-analysis.